Mental health and the healthy immigrant effect in Chile: a comparative cross-sectional study with international migrants and locals - Blukacz, Alice; Marcela Oyarte; CABIESES VALDES, BALTICA BEATRIZ; Paula Madrid; OBACH KING, ALEXANDRA ALICE (Frontiers Media SA, 2025)
IntroductionThe question of whether international migrants appear to be in better health than the locals, and whether this “healthy immigrant effect” declines over time is a highly relevant one, especially with regards to mental health. Based on a community-based survey conducted in Santiago, Chile, this study compares the mental health outcomes of international migrants versus local populations and examines differences within the international migrant group of respondents.MethodsObservational cross-sectional study. Data was collected with international migrants and Chilean participants in 2021–2022 through a structured questionnaire. The study examined self-reported stress and mood disorders in relation to demographic, socioeconomic, health, and migration-related factors. Descriptive analyses were conducted for all variables overall and stratified by perceived stress, mood disorders, and migration status. Associations were assessed using Chi-square or Fisher’s exact tests, with Cramer’s V used to evaluate effect size. Multiple imputation (m = 5) addressed missing data using the mice package in R, followed by generalised logistic regression models fitted across imputed datasets and combined using Rubin’s rules; stepwise selection based on AIC was used for variable reduction, and models were run for the full sample and separately for the migrant population.ResultsThe sample included 1,656 international migrants and 1,664 locals. Being a migrant was negatively associated with reporting stress and mood disorders in all analyses. Among migrants, the main risk factors for stress were perceiving a high number of migrants in the neighbourhood and having experienced abuse as a migrant and for mood disorders the main risk factor was reporting having experienced abuse as a migrant as well as a longer stay in Chile.DiscussionWe found a healthy immigrant effect for mental health among international migrants in Chile, which declined over time in the case of mood disorders. Chilean participants reported very high levels of mental health issues, consistent with existing studies. However, results for international migrants highlight both risk and protective factors linked to migration processes, which are unique to them, warranting a specific approach to their mental health needs.